GENETIC INSIGHTS INTO METABOLIC SYNDROME: VITAMIN D RECEPTOR BSMI POLYMORPHISM AMONG THE INDIGENOUS PEOPLE OF MANIPUR - A SAPNA DEVI; NARMADA THONGAM; SUCHITRA CHONGTHAM (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objectives of this study were to determine the association between the BsmI (rs1544410) polymorphism in the Vitamin D receptor (VDR) gene and metabolic syndrome (MetS) among the Indigenous population of Manipur. Methods: A cross-sectional study total of 200 participants were genotyped for the BsmI polymorphism using polymerase chain reaction-restriction fragment length polymorphism analysis. Clinical parameters such as fasting blood sugar (FBS), lipid profile, blood pressure (BP), and Vitamin D were assessed. Results: Statistical analysis revealed a significant association between the BsmI polymorphism and FBS levels, suggesting a potential genetic predisposition to impaired glucose metabolism. BB genotype is associated with higher FBS, cholesterol, triglycerides, and BP, which are risk factors for MetS. BB genotype also has significantly lower Vitamin D levels, which may play a role in these metabolic disturbances. Conclusion: Individuals with the heterozygous (Bb) and homozygous recessive (bb) genotypes exhibit more favorable metabolic parameters compared to those with the homozygous dominant (BB) genotype. These findings highlight the role of VDR gene variants in MetS and underscore the need for further studies to validate these results in larger populations. Understanding genetic risk factors can contribute to personalized prevention and therapeutic strategies for MetS, particularly in genetically distinct ethnic groups like Manipur.